Serum MDA and Vitamin C level in Conversion Disorder Patients - Karim, Rubaba; Nahar, Zabun; Islam, Mohammad Safiqul; Ahmed, Maizbha Uddin; Mustafa, AGM; Shohag, Md Hasanuzzaman; Maruf, Abdullah Al; Hasnat, Abul (Dhaka University Journal of Pharmaceutical Sciences, 2012)
In the present study serum Malondialdehyde (MDA) and Vitamin C profiles of conversion disorder patients were compared with control and evaluated the correlation between MDA and vitamin C level was evaluated with their socioeconomic factors. Conversion disorder patients (n=45), age ranging from 17 to 41 years, were randomly recruited from the Department of Psychiatry, Bangabandhu Sheikh Mujib Medical University Hospital, Dhaka, Bangladesh for this study. Control group also included 45 healthy individuals matched by the socio-demographic status to that of the patients. Blood samples were analyzed for determining MDA and vitamin C using Ultraviolet-Visible (UV-VIS) spectroscopy. Serum concentrations of MDA and vitamin C of conversion disorder patients were 2.19 ± 1.47 and 19.23 ± 5.59 μmol/L respectively while these were 2.11 ± 0.88 and 21.00 ±4.96 μmol/L in control subjects respectively. Socioeconomic data revealed that most of the patients were young female and unmarried. The mean BMI of patients (21.05 ± 3.39) were not significantly different (P > 0.05) from the control subjects (20.86 ± 1.86). Moreover, statistical analysis revealed that there were no significant correlation between MDA, vitamin C concentrations and socioeconomic factors. The results of our study have shown higher oxygen free radical production, evidenced by increased levels of MDA and decreased levels of ascorbic acid which supports the oxidative stress in conversion disorder patients. DOI: http://dx.doi.org/10.3329/dujps.v10i1.10017 DUJPS 2011; 10(1): 59-64